Pentingnya Dialog Antaragama dalam Konteks Pandemi COVID-19 - nadya wahyu ratnawati; Nur azka wahida (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
The COVID-19 pandemic is a reality that impacts and impacts people's lives. This is a complex and urgent situation that needs to be addressed. Even though the global health crisis has been declared over, this pandemic situation is not truly over. To answer this, a response from religious communities is needed, and the response is dialogue. The aim of this research is to highlight the importance of dialogue between religious communities in a pandemic situation. Therefore, the author uses qualitative methods with a library research approach. The author considers dialogue between religious communities to be important in this pandemic problem. The country has a model of reciprocity, mutual transformation and acceptance, as well as an awareness of global responsibility in interfaith dialogue. That is why dialogue plays an important role in motivating people to think and act for good in a pandemic situation.